2015
DOI: 10.1159/000435961
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Test Abnormalities in Pediatric Inflammatory Bowel Disease

Abstract: Background: Pulmonary involvement in adult patients with inflammatory bowel disease (IBD) seems more common than previously appreciated. Its prevalence and development over time in pediatric IBD patients are largely unknown. Objectives: The aim was to study lung function including fraction of exhaled nitric oxide (FeNO) and transfer capacity for carbon monoxide (TLCO) in pediatric IBD patients and to describe the longitudinal development in a subset of patients with lung function abnormalities. Methods: Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…A recent study showed alterations in certain parameters of PFT (forced expiratory volume in 1 s (FEV1), forced vital capacity and diffusion capacity of lung for carbon monoxide (DLCO)) between the day of IBD diagnosis and three years after [128]. Contradictory to other studies, Furlano et al showed that pediatric CD patients have significantly decreased mid-and end-expiratory flow values, but the number of patients with flow values under the norm was generally low [98].…”
Section: Pulmonary Function and Breathing Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study showed alterations in certain parameters of PFT (forced expiratory volume in 1 s (FEV1), forced vital capacity and diffusion capacity of lung for carbon monoxide (DLCO)) between the day of IBD diagnosis and three years after [128]. Contradictory to other studies, Furlano et al showed that pediatric CD patients have significantly decreased mid-and end-expiratory flow values, but the number of patients with flow values under the norm was generally low [98].…”
Section: Pulmonary Function and Breathing Testsmentioning
confidence: 97%
“…In most of the published cases of children with IBD and pulmonary symptomatic PM, X-rays showed alterations (Tables 1 and 2). If the airway system is affected in children with IBD, the inflammation concentrates on smaller airway compartments, leading to purulent bronchitis [18,86,98]. Adult IBD patients with small airway involvement tend to be younger and the proportion of PM, which occurs before intestinal symptoms, is higher than in those patients with large airway involvement [96].…”
Section: Clinical and Radiological Findingsmentioning
confidence: 99%
“…Most studies on respiratory manifestations of IBD in children include lung function testing. To date, there are six studies that assessed lung function in 294 children with IBD [14,48,[54][55][56][57]. Pulmonary function abnormalities were generally inconsistent and mild.…”
Section: Lung Function Abnormalitiesmentioning
confidence: 99%
“…Another hypothesis is that late pulmonary involvement reflects the reduction of immunosuppression after surgery allowing pulmonary disease to flare up [ 36 , 47 ]. It could also be speculated that disease activity is not necessarily synchronous among the involved organs, as reflect by abnormal pulmonary findings among IBD patients in clinical intestinal remission [ 48 ].…”
Section: Pulmonary Side-effects Of Ibd Therapiesmentioning
confidence: 99%
“…FeNO could provide a quantitative and qualitative indicator of respiratory airway inflammation [ 29 ], as it is routinely used to screen and manage asthmatic patients [ 30 ]. Pilot studies have highlighted the possible use of FeNO in systemic inflammatory nonpulmonary diseases [ Table 1 ] [ 31 34 ], such as psoriasis. In this review, we describe the rationale and possible applications of FeNO in the management of PS.…”
Section: Introductionmentioning
confidence: 99%